Vegetation composition and diversity of highland peats in Toba Plateau, North Sumatra, Indonesia - S.M. Rezaul Karim; Taufiq Siddiq Azvi; Mashhor Mansor (Academic Journals, 2011)
The study was conducted at Humbang Hasundutan of Toba Plateau in North Sumatra, Indonesia to determine the vegetation composition and plant diversity of the highland peat. Four sampling plots of size 100 x 100 m were selected based on landscape usages in the study area and the plots were further divided into 400 subplots each measuring 10 x 10 m. On the basis of habitat characters and human activities, the total sampling area were categorized into five groups, namely flooded area, dried area, mining area, pine forest and agriculture area. All the vegetation under different areas was collected and identified. The vegetations were then grouped into different plant types, trees, shrubs and herbs. They were also classified as native or invasive species according to their severity and invasiveness. Diversity index and evenness of species were determined. The similarity between different sampling areas in respect of species composition was also measured. A total of 60 plant species from 40 families were identified. Dry area contained 55 species from 38 families; flooded area had 24 species from 19 families, while mining area had 10 species from 8 families. 18 species from 16 families were recorded from pine forest and 10 species from 9 families were found in agriculture area. The family Polypodiaceae had the highest number of species consisting of 6 species followed by Asteraceae and Ericaceae with 4 species each. The families Cyperaceae and Euphorbiaceae had 3 species each. The families Araliaceae, Lycopodiaceae, Moraceae, Myrtaceae and Theaceae consist of 2 species, and the other families recorded with only 1 species. 2 species of fern, Dicranopteris pubigera (Gleichiniaceae) and Blechnum indicum (Blechnaceae) were recorded from all the sampling areas. The highest diversity index was from dry area (2.268) and the lowest was from mining area (0.81). Among the species recorded, invasive weedy species were higher in number (68%) in comparison to native species (32%). Based on modified Morisita’s similarity index, the vegetation at Toba highland peat can be divided into two main groups. The first group is composed of dry area and pine forest, which differed from other group (similarity index = 0.058) which includes mining area, agriculture area and flooded area. Within the second group, agriculture area and mining area was very similar with similarity index 0.895. Again these two areas were also closely similar to the flooded area (similarity index = 0.707).